Experience in the use of invasive hemodynamic monitoring using prepulmonary and transpulmonary thermodilution in lung transplantation - A. M. Talyzin; S. V. Zhuravel; M. Sh. Khubutiya; E. A. Tarabrin; N. K. Kuznetsova (Вестник трансплантологии и искусственных органов)
Objective: to demonstrate the experience of using complex hemodynamic monitoring by means of prepulmonary thermodilution (PPTD) and transpulmonary thermodilution (TPTD) – PiCCO – in lung transplantation (LTx). Materials and methods. Presented is a clinical case study of a 51-year-old patient with the following diagnosis: severe bronchiectasis and type 3 respiratory failure. Bilateral lung transplantation was performed at Sklifosovsky Research Institute for Emergency Medicine, Moscow. Intraoperative hemodynamic monitoring was performed using PPTD and TPTD techniques. Conclusion. The case study presented shows that simultaneous use of PPTD and TPTD for hemodynamic monitoring during lung transplantation achieves better treatment outcomes. This hemodynamics monitoring strategy is highly informative, allows for continuous measurement of necessary hemodynamic parameters and for timely and targeted correction of identified disorders by influencing the basic pathogenesis links of cardiovascular disease.